A first attempt for using of combined sorption and anaerobic processes for handling source separated human urine - Beler-Baykal, B.; Taher, Mustafa N.; Altinbas, M. (Elsevier BV, 2022)
Processing human urine with clinoptilolite results in a solid phase upon which majority of nutrients are concentrated, which may be used as fertilizer; in addition to a liquid residue to be disposed of which is saline, rich in organics and contains residual nutrients. Despite several work regarding nutrients recovery from human urine, the fate of organic matter in the liquid residue is yet to be revealed. This study aims to investigate the combination of sorption and anaerobic processing (ANA) to accomplish concurrent nutrient recovery, and organic matter removal from hydrolyzed human urine (HHU) for environmental protection. Fixed bed clinoptilolite columns were used for nutrient recovery from HHU and an anaerobic expanded granular sludge bed reactor (AnEGSB) was used for removal of organic matter from residue of the former process. Furthermore, the effluent of AnEGSB was subjected to post treatment using stage-wise sorption to enhance the effluent quality before disposal. Majority of nutrients were removed by the sorption process with 80% of ammonium and almost all of phosphorus. Sorption removed 35% of orgnic matter while ANA was responsible for the rest. Post treatment helped to polish the quality of the AnEGSB effluent to the permissible level of domestic wastewater discharge standards of EU.With the proposed combination, almost 100% of nitrogen and phosphorus were recovered for further use as fertilizer providing benefits for sustainability. Also, 97% of organic matter could be removed from HHU to provide environmental protection, which was accompanied by methane (CH4) production of 0.4 L CH4/day which is equivalent to 0.113 L CH4/g COD removed. Successful implementation of the proposed combination helps improve management of domestic wastewater.
Keywords: Sewage; Nitrogen; Wastewater; Waste Disposal, Fluid; Bioreactors; Humans; Anaerobiosis